Top-Down Implementation of the Job Creation Law: Reforming Environmental Impact Assessment Policy and Implications for Environmental Governance in Indonesia - Ayyasi, Sofi; Shahirah, Nur Syofi; Cahyani, Ni Luh Viya Anggun; Arjuna, Briean Sandika; Siregar, Agatha Cristy; Raja, Inggrid Sisilia Lumban (Journal Governance Bureaucratic Review, 2025)
Indonesia’s Job Creation Law (Law No. 11 of 2020) represents a major reform in national environmental governance aimed at streamlining bureaucracy and accelerating investment; however, it has simultaneously raised concerns about ecological accountability and public participation. This study examines how the top-down implementation of the law has reshaped Environmental Impact Assessment (EIA) procedures and the broader structure of environmental governance. The research aims to analyze the implications of bureaucratic simplification, centralization of authority, and restricted public engagement for sustainable policymaking. Employing a qualitative descriptive-analytical approach, the study collected data from legal documents, policy briefs, and interviews with governmental and civil society actors to explore institutional dynamics across central and regional levels. Findings indicate that while risk-based licensing and the Online Single Submission (OSS) system have improved efficiency and coherence in licensing processes, they have concurrently weakened preventive oversight, diminished local autonomy, and curtailed participatory mechanisms. The centralization of decision-making has standardized procedures but reduced flexibility and contextual responsiveness, leading to governance gaps between policy design and local execution. Moreover, the narrowing of public involvement in EIA processes has eroded transparency and legitimacy, undermining the principles of democratic environmental governance. The study concludes that the effectiveness of top-down implementation remains contingent upon institutional capacity, intergovernmental coordination, and inclusivity. It recommends adopting a hybrid governance model that combines hierarchical efficiency with participatory accountability to ensure that economic reform aligns with ecological sustainability and social legitimacy in Indonesia’s environmental policy landscape